2018
DOI: 10.1111/ene.13839
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate and teriflunomide for multiple sclerosis in a real‐life setting: a French retrospective cohort study

Abstract: Background and purpose Dimethyl fumarate (DMF) and teriflunomide are approved oral disease‐modifying treatments for relapsing‐remitting multiple sclerosis (MS). Phase 3 trials established these agents to be effective and generally well tolerated, although comparative efficacy and discontinuation rates are still unknown. The aim of this study was to assess real‐world efficacy and discontinuation of DMF and teriflunomide in patients with relapsing‐remitting MS. Methods This retrospective observational cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 9 publications
4
13
0
1
Order By: Relevance
“…Nevertheless, we examined clinical and MRI lesion activity measures in a post-hoc analysis between the two treatment groups. In line with several recent comparative effectiveness real-world studies between TFM and DMF [28,49,50], but contrary to others [51,52], we did not find any significant clinical (relapse rate and change in EDSS score) or MRI (new/enlarging T2 lesions, T1 pre- and post-contrast lesions and their volumes) differences between the two treatment groups in the current study. There were no unexpected safety signals for either treatment and the discontinuation rate was similar between the two treatment arms, as reported recently [53].…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, we examined clinical and MRI lesion activity measures in a post-hoc analysis between the two treatment groups. In line with several recent comparative effectiveness real-world studies between TFM and DMF [28,49,50], but contrary to others [51,52], we did not find any significant clinical (relapse rate and change in EDSS score) or MRI (new/enlarging T2 lesions, T1 pre- and post-contrast lesions and their volumes) differences between the two treatment groups in the current study. There were no unexpected safety signals for either treatment and the discontinuation rate was similar between the two treatment arms, as reported recently [53].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, nearly 40% of patients with a single relapse and RR‐MS patients who were previously treated, stopped their DMT due to side effects, and stayed untreated thereafter. Although many DMTs are available, with minimal side effects for many patients, reducing the side effects of a first‐line DMT is still a major challenge for improving persistence with treatment [20,21]. This partially explains why 8% of RR‐MS patients had previously been treated with a median of two different DMTs, and were no longer being treated.…”
Section: Discussionmentioning
confidence: 99%
“…The lower risk of discontinuation because of treatment failure among dimethyl fumarate users suggests that this therapy was more effective, as shown by others. [9][10][11] One study comparing dimethyl fumarate to teriflunomide reported a significantly lower annualized relapse rate during a 2-year period. 9 In a time-to-event study, a lower risk of relapses after 38 months was found for dimethyl fumarate in comparison with teriflunomide.…”
Section: Discussionmentioning
confidence: 99%
“…6 Dimethyl fumarate and teriflunomide have not been compared directly, but real-world studies comparing both efficacy and discontinuation rates have been presented recently with mixed results. [7][8][9][10][11] Variables associated with discontinuation have rarely been evaluated in these studies.…”
Section: Introductionmentioning
confidence: 99%